Myoelectric stimulation on gluteus medius or biceps femoris reduced knee valgus torque during a forward landing task - Fong, D. T. P.; Wang, M.; Chu, V. W. S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Anterior cruciate ligament injury can be caused by excessive knee valgus torque. This study demonstrated the effect of myoelectric stimulation to the gluteus medius and biceps femoris on the reduction of knee valgus torque. Twelve females performed a forward drop landing task in a biomechanics laboratory. A 130V myoelectric stimulation was delivered to either or both the gluteus medius and biceps femoris through electrodes of different size (38 or 19 cm2) when the subject landed. A motion analysis system was used to obtain the normalized knee valgus torque data. Results showed a significant drop from 15.7 Nm to 11.0-11.4 Nm in stimulating either one muscle with the big electrodes. The technology could be a new option to be implemented as active functional sport apparel for the prevention of sport-related injury induced by knee valgus spraining motion.